The Influence of Recruitment on Onboarding Programs, Mentoring Programs and Their Impact on Employee Performance at PT Borwita Citra Prima, Makassar City - Muh, Astang; Nursyamsi, Idayanti; Hakim, Wardani (The Scientia Law and Economics Review, 2023)
This study aims to test and analyze the influence of recruitment on onboarding programs , mentoring programs and their impact on employee performance. The object of this study is PT Borwita Citra Prima, Makassar City, with a total of 102 respondents consisting of sales, delivery van, delivery presale and warehouse . Data collection was conducted by distributing questionnaires and testing research hypotheses using the IBM Statistical Package for Social Sciences (SPSS) analysis tool with path analysis techniques. The results of the study show that: First, recruitment has a positive and significant effect on the onboarding program . Second, recruitment has a positive and significant effect on the mentoring program. Third, recruitment has a positive and significant effect on employee performance. Fourth, the onboarding program has a positive and significant effect on employee performance. Fifth, mentoring program has a positive and significant effect on employee performance. Sixth, onboarding program significantly mediates recruitment to employee performance. Seventh, mentoring program significantly mediates recruitment to employee performance.